1997
DOI: 10.2307/2269439
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Cyclic in Forest and Grass Ecosystems Irrigated with 15 N-Enriched Wastewater

Abstract: Nitrogen cycling was studied during the first 2 yr of spray irrigation of vegetation by treated wastewater in Falmouth (Cape Cod), Massachusetts. We attempted to take advantage of an unexpected natural 15 N enrichment during wastewater treatment to trace the fate of wastewater N following irrigation. Wastewater N was enriched by 6-20‰ relative to soil and by 13-25‰ relative to vegetation. We were able to estimate retention of wastewater N by soil using a mass balance of 15 N. However, under conditions of N sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 24 publications
2
34
0
2
Order By: Relevance
“…Changes in abundance and composition of understory shrubs and herbs might also be expected in response to N deposition, as has been shown in Europe (Bobbink et al 1998). In the eastern United States the data are not as clear;the few studies that have examined this effect have used fertilization experiments as opposed to gradient studies or long-term measurements, and the studies have shown varying responses (Jordan et al 1997;Hurd et al 1998;Rainey et al 1999;Gilliam et al 2006). It is known from studies in the eastern United States that N addition shifts the activity of soil microorganisms, with some responding positively to N addition, while others respond negatively (e.g., Carreiro et al 2000).…”
Section: Forestsmentioning
confidence: 99%
“…Changes in abundance and composition of understory shrubs and herbs might also be expected in response to N deposition, as has been shown in Europe (Bobbink et al 1998). In the eastern United States the data are not as clear;the few studies that have examined this effect have used fertilization experiments as opposed to gradient studies or long-term measurements, and the studies have shown varying responses (Jordan et al 1997;Hurd et al 1998;Rainey et al 1999;Gilliam et al 2006). It is known from studies in the eastern United States that N addition shifts the activity of soil microorganisms, with some responding positively to N addition, while others respond negatively (e.g., Carreiro et al 2000).…”
Section: Forestsmentioning
confidence: 99%
“…In the northwest region around the LWRP, nitrate isotope data confirm that the shallow wells here have a different nitrate source than in the rest of the study area (Figure 9). Shallow nitrate-δ 15 N values are between 13.0‰ and 29.2‰, in the range expected for treated wastewater effluent (Jordan et al, 1997;Griggs et al, 2003), and nitrate-δ…”
Section: Nitrate Sources Applied Wastewatermentioning
confidence: 78%
“…At present, the 15 N trace technique has been proved useful as an tool for studying the ecological effects of N input on ecosystem. Jordan et al (1997) studied the N cycling in forest and grass ecosystems irrigated with 15 N-enriched wastewater in Falmouth, and found that under conditions of N saturation, δ 15 N values for plants were lower, possibly due to discrimination against 15 N during uptake of NH 4 + and NO 3 -by plant roots. Moreover, the capacity of soil N retention fell rapidly as the forest and grass ecosystems became N saturated, and N leaching losses greatly increased.…”
Section: Ecological Effects Of Nitrogen Input On Ecosystemmentioning
confidence: 99%